2011
DOI: 10.1002/jbmr.499
|View full text |Cite
|
Sign up to set email alerts
|

Bone microarchitecture assessed by TBS predicts osteoporotic fractures independent of bone density: The manitoba study

Abstract: The measurement of BMD by dual-energy X-ray absorptiometry (DXA) is the ''gold standard'' for diagnosing osteoporosis but does not directly reflect deterioration in bone microarchitecture. The trabecular bone score (TBS), a novel gray-level texture measurement that can be extracted from DXA images, correlates with 3D parameters of bone microarchitecture. Our aim was to evaluate the ability of lumbar spine TBS to predict future clinical osteoporotic fractures. A total of 29,407 women 50 years of age or older at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
384
9
23

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 540 publications
(449 citation statements)
references
References 40 publications
33
384
9
23
Order By: Relevance
“…(20)(21)(22) Indeed, previous studies demonstrated that TBS is strongly correlated with bone microarchitecture, regardless of BMD, (23) and documented the added value of TBS in bone mineral densitometry for fracture risk assessment in postmenopausal osteoporosis. (24)(25)(26)(27) We found that TBS, but not LS-BMD, is associated with prevalent vertebral fractures regardless of age, BMI, and gender. More importantly, in a subgroup of patients followed over time, TBS was able to predict incident fractures independently of LS-BMD and age, BMI, and gender.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…(20)(21)(22) Indeed, previous studies demonstrated that TBS is strongly correlated with bone microarchitecture, regardless of BMD, (23) and documented the added value of TBS in bone mineral densitometry for fracture risk assessment in postmenopausal osteoporosis. (24)(25)(26)(27) We found that TBS, but not LS-BMD, is associated with prevalent vertebral fractures regardless of age, BMI, and gender. More importantly, in a subgroup of patients followed over time, TBS was able to predict incident fractures independently of LS-BMD and age, BMI, and gender.…”
Section: Discussionmentioning
confidence: 60%
“…(20)(21)(22) TBS has been demonstrated to be strongly correlated with bone microarchitecture, regardless of BMD, (23) and several studies (24)(25)(26) have documented the added value of TBS in bone mineral densitometry for fracture risk assessment in postmenopausal osteoporosis. (22)(23)(24)(25)(26)(27) Few data are available regarding TBS in patients with glucocorticoid induced osteoporosis, (28,29) and no studies evaluated bone microarchitecture by TBS in SH patients.…”
Section: Introductionmentioning
confidence: 99%
“…(21) Its primary value beyond BMD is that it may specifically assess some dimensions of vertebral bone microarchitectural texture, which is recognized to be an important determinant of bone strength independent of BMD. ( (17,18) and mCT (35 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported precision for TBS ranged between 1.48% (in-house data) and 2.1%. (21) At the Department of Osteoporosis of the University Hospital of Berne, the coefficient of variation for LS BMD measurements assessed in accordance with ISCD recommendations (15 outpatients representative of daily routine with triplicate measurements after repositioning) is 0.90% with a corresponding coefficient of variation of 1.12% for TBS. Thus, the least significant change (LSC) is 2.49% for LS BMD and 3.10% for TBS.…”
Section: Measurement Of Tbsmentioning
confidence: 99%
See 1 more Smart Citation